A nova autoimagem dos usineiros no Nordeste brasileiro / The new self-image of sugar mill owners in the Brazilian Northeast / La nueva autoimagen de los empresarios de la caña en el Noreste brasileño - Bezerra, Lucas (REVISTA NERA, 2023)
The article analyzes the 'new' ideological face of the sugarcane mill owners in the northeastern 'sugarcane zone', formed by the three main producing states of the region: Alagoas, Pernambuco and Paraíba. It is argued that this traditional segment of the dominant classes in the countryside has experienced, over the course of the last two decades, transformations that have broadened its internal composition and accommodated it to the dynamics of agribusiness. Thus, they have shaped a new rhetoric, based on the defense of sugarcane monoculture as an agro-social business, resorting to notions such as sustainability and social and environmental responsibility. The limits and contradictions of this discourse are problematised in the light of class conflicts and the political-ideological dimension contained within them, which can explain the reasons why the sugarcane farmers, through their representative bodies, seek social legitimacy for the full exercise of their economic activity. Methodologically, we made use of research into documents from employers' organizations in the region, as well as direct dialogue with their leaders by means of interviews.